2020
DOI: 10.1002/ppul.25057
|View full text |Cite
|
Sign up to set email alerts
|

Using a home oxygen weaning protocol and pCO2 to evaluate outcomes for infants with bronchopulmonary dysplasia discharged on home oxygen

Abstract: Background Predischarge capillary blood gas partial pressure of carbon dioxide (pCO2) has been associated with increased adverse events including readmission. This study aimed to determine if predischarge pCO2 or 36‐week pCO2 was associated with increased respiratory readmissions or other pulmonary healthcare utilization in the year after neonatal intensive care unit (NICU) discharge for infants with bronchopulmonary dysplasia (BPD) discharged with home oxygen, using a standardized outpatient oxygen weaning pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…BPD was defined as respiratory support at 36 weeks postmenstrual age. [7][8][9] Infants with tracheostomies and surgical nonrespiratory comorbidities were excluded; only one member of a multiple gestation was included.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…BPD was defined as respiratory support at 36 weeks postmenstrual age. [7][8][9] Infants with tracheostomies and surgical nonrespiratory comorbidities were excluded; only one member of a multiple gestation was included.…”
Section: Methodsmentioning
confidence: 99%
“…Home oxygen is weaned using a structured algorithm, which has been previously published. 7 We also have a standardized guideline for the management of diuretics. This algorithm is based on the most common diuretics that the infants are discharged home on which include chlorothiazide, hydrochlorothiazide, and combined spironolactone/hydrochlorothiazide.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 Most providers utilize nighttime oxyhemoglobin saturations from oximetry to wean oxygen. 13 There are recent studies describing utilizing recorded home oximetry in an oxygen weaning protocol in place of a PSG, 31 but there are no published reports describing the desaturation index despite the link to the apnea −hypopnea index on PSG. 15 A recent report described employing downloadable home oximetry information to assist with weaning oxygen therapy at home outside of in-person visits, but this system requires the software, staffing resources, and monitoring available, as well as frequent family participation.…”
Section: Discussionmentioning
confidence: 99%
“…Infants using this protocol are weaned from HOT in a median of 21 weeks after NICU discharge. 9 Prior studies have demonstrated that parental engagement and comfort in weaning HOT has a dose-dependent effect on the duration of HOT. 10 While we have a well-established outpatient protocol for weaning HOT, we noticed that poor preparedness with HOT led to problems on discharge.…”
Section: Introductionmentioning
confidence: 99%